Changes in the Patterns of Poverty Duration in Germany, 1992–2009. (11th September 2014) - Kyzyma, Iryna
Abstract : Using data from the German Socio‐Economic Panel, this study explores how the duration of poverty and its determinants evolved in Germany between the early 1990s and the late 2000s. To do this, we split the overall period of interest into a set of six‐year long rolling windows and use them to document changes in the incidence and length of poverty episodes over time. A joint modeling of poverty and non‐poverty spells controlling for unobserved heterogeneity is applied within each window in order to uncover how poverty experiences of individuals with different socio‐economic characteristics have evolved over time. The results indicate that poverty has become more persistent and recurrent in Germany since the beginning of the 1990s. Individuals living in households whose head is a citizen from a European Union country, or has general or vocational training, partially improved their situation over time whereas those over 55 years old, households with a disabled or uneducated head, and single parent households became more prone to poverty.